Home was not a safe haven: women's experiences of intimate partner violence during the COVID-19 lockdown in Nigeria - Olufunmilayo I. Fawole; Omowumi O. Okedare; Elizabeth Reed (BMC, 2021)
Abstract Background Emergency situations, including epidemics, increase incidence of violence against women, especially intimate partner violence (IPV). This paper describes specific scenarios of IPV reported by women during the COVID-19 pandemic in Nigeria to provide insight for policy and programmatic efforts. Methods This paper draws on seven de-identified case reports from organisations serving women experiencing IPV as well as media coverage of IPV cases in Nigeria, between April and May, 2020. Results In most cases, reports identified IPV that was occurring prior to the lockdown, but increased in severity or involved new types of violence during the lockdown. The case scenarios included descriptions of many forms of IPV commonly reported, including physical, economic, psychological and sexual violence, often concurrently. Several women also reported threats of being thrown out of their homes by perpetrators, which threatens women's ability to protect themselves from exposure to COVID-19, but could also leave women stranded with no access to transportation, social services, or other resources during the lockdown. Several women also reported IPV that involved custody of children, as well as IPV that disrupted women's income generation. IPV was also reported in relation to economic stressors associated with the lockdown. Reports highlight how the lockdown disrupted women's social support, hindering accessibility of formal and informal sources of help. Conclusion The lockdowns in Nigeria may have inadvertently placed women already experiencing partner violence at risk for experiencing more severe violence, new challenges to cope with violent experiences, and other forms of violence, including violence that used the lockdown as a way to threaten women's security and ability to protect themselves from the virus. Hence, there is need for innovative approaches to support victims, with emphasis on ways in which perpetrators of IPV may be using the threat of COVID-19 to further gain power and control over partners.